Exploring the Servant Leadership, Work Engagement, and Public Service Motivation among Civil Servants’ Sport Council of Ministry of Interior in the Cambodian Setting - Kimseng Sok; Sarom Mok; Mengheang Hor; Sothea Lim (Jurnal Locus Penelitian dan Pengabdian, 2026)
Public mistrust and growing aspirations for legitimacy in public administration characterize Cambodia's institutional environment. This quantitative study with a non-experimental design aimed to investigate the relationships between servant leadership, work engagement, public service motivation, and healthy organizational outcomes in the Cambodian public sector within the framework of the Job Demands–Resources (JD-R) theory and the Healthy and Resilient Organizations (HERO) model, taking into account the moderating effect of the supervisor's gender. Using established instruments, this study evaluated servant leadership, public service motivation, work engagement, and organizational results in a sample of 280 civil servants from the Ministry of Interior's Sport Council selected through convenience sampling technique. The five hypotheses were validated through structural equation modeling: servant leadership was positively correlated with public service motivation (B= 0.18, p < 0.001) and work engagement (B= 0.15, p= 0.002), while work engagement was positively correlated with healthy organizational outcomes (B= 0.47, p < 0.001), demonstrating partial mediation effects among these variables. The supervisor's gender did not have any moderating influence on the proposed relationships. In addition to highlighting the importance of servant leadership as a crucial social resource for promoting motivation, work engagement, and organizational well-being within the particular context of Cambodian public institutions, this study offers empirical evidence on the motivational mechanisms functioning within the public sector. The findings contribute to the integration of JD-R theory and the HERO model in public administration research, providing practical implications for developing more inclusive and healthy organizations in the Cambodian public sector.